IMPLEMENTASI PEMBELAJARAN BERBASIS MASALAH TERHADAP PENINGKATAN KEMAMPUAN BERFIKIR KRITIS SISWA (Penelitian Eksperimental pada Pembelajaran IPA Kelas III SDN 188 Pekanbaru) - Cindi Laudia; Mahmud Alpusari; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Problem based learning as inovation on learning because on problem based learning thinking achievement by eptimaly students can developing, assessing, testing and developing achievement of continue thinking. Research using experiment method (Quasi Experimental design) has a purpose to knowing impact of problem based learning to improvement of achievement critical thinking by students on learning IPA grade III SDN 188 Pekanbaru and to knowing differential improvement achievement critical thinking between experimental class with control class. Based on result of this research have got achievemet critical thinking within problem based learning, differential improvement from experimental class and control class, in experimental class improvement of average value from 60,778 be 85,667 with gain indeks 0,639 with ordinary cathegory. In other hand in control class have improvement skor achievement critical tinking of student by 65,143 be 75,429 with average gain indeks 0,262 in low chategory.Applied problem based learning given impact on improvement achievement critical tinking by students SDN 188 Pekanbaru. This result based on determination coefisient is0,342%. This is describes about determination coefisient low.Key Word: Problem Based Learning, Achievement Critical Thinking.